Plasma extracellular vesicle protein content for diagnosis and prognosis of global cardiovascular disease - Wang, J. W. (2015)
Cardiovascular disease is a major public health problem worldwide. Its growing burden is particularly ominous in Asia, due to increasing rates of major risk factors such as diabetes, obesity and smoking. There is an urgent need for early identification and treatment of individuals at risk of adverse cardiovascular events. Plasma extracellular vesicle proteins are novel biomarkers that have been shown to be useful in the diagnosis, risk stratification and prognostication of patients with cardiovascular disease. Ongoing parallel biobank initiatives in European (the Netherlands) and Asian (Singapore) populations offer a unique opportunity to validate these biomarkers in diverse ethnic groups.